2021
DOI: 10.1021/acs.chemmater.1c00857
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Synthesis of Single-Layer Quasi-Ruddlesden–Popper Phase Bismuth-Based Two-Dimensional Perovskite Nanosheets with Controllable Optoelectronic Properties

Abstract: Single- and few-layered two-dimensional (2D) nanomaterials have attracted intense research interest in the last two decades due to their unique electronic and optoelectronic properties leading to various potential applications. Herein, we report the colloidal synthesis of Bi-based 2D perovskite nanosheets (PEG6-NH3 +) n Cs3–n Bi2X9, where X = Cl, Br, and I, through careful design of reaction conditions and selection of poly­(ethylene glycol) (PEG6) surface passivating ligands. The 2D nanosheets are ∼5 nm in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
(82 reference statements)
0
5
0
Order By: Relevance
“…Fine structure analysis showed that as the number of acid ligands increased, layered structures gradually emerged, which were quite similar to those in 2D layered hybrid perovskite materials (Figure 4f ). [72][73][74][75][76] The distance between layers was then identified as 2 times the ligand length, indicating a Ruddlesden-Popper configuration. [77] In addition, the TOPO-mediated one-step approach proved effective for the formation of 2D nanoplatelets and superlattices using FAPbBr 3 (FA = formamidine).…”
Section: Capping Ligandsmentioning
confidence: 99%
“…Fine structure analysis showed that as the number of acid ligands increased, layered structures gradually emerged, which were quite similar to those in 2D layered hybrid perovskite materials (Figure 4f ). [72][73][74][75][76] The distance between layers was then identified as 2 times the ligand length, indicating a Ruddlesden-Popper configuration. [77] In addition, the TOPO-mediated one-step approach proved effective for the formation of 2D nanoplatelets and superlattices using FAPbBr 3 (FA = formamidine).…”
Section: Capping Ligandsmentioning
confidence: 99%
“…We have also investigated related work about synthesis of 2D Cs 3 Bi 2 Br 9 nanoflakes, including the hot injection method, [20] the antisolvent recrystallization method [21] and the wet-chemical method. [39] However, the hot injection method is effective for synthesizing Cs 3 Bi 2 Br 9 quantum dots with sizes smaller than 10 nm; the in-plane size of Cs 3 Bi 2 Br 9 prepared by antisolvent recrystallization method is about 200 nm, which is still too small for device application; the wet-chemical method could synthesize Cs 3 Bi 2 Br 9 with about 10 μm in-plane size, but the thickness is about 500 nm and unevenly distributed.…”
Section: Synthesis and Characterization Of 2d Cs 3 Bi 2 Br 9 Nanoflakesmentioning
confidence: 99%
“…[15][16][17][18] As a typical A 3 B 2 X 9 structure, 2D Cs 3 Bi 2 Br 9 possesses ideal electronic structure, direct bandgap, long carrier diffusion length and high light absorption, rendering it an excellent candidate for applications in photodetectors, solar cells and light-emitting diodes. [19][20][21][22] Combined with large effective atomic number, high resistivity (10 7 -10 12 Ω cm) and high density (4.7 g cm −3 ), 2D Cs 3 Bi 2 Br 9 has been widely applied to detect X-ray. [23][24][25] Furthermore, large-size 2D Cs 3 Bi 2 Br 9 nanoflakes not only have lower bulk defects, higher carrier mobility and longer carrier lifetime, allowing for the excited electrons or holes to drift the device channel quickly, but also is compatible with integrated X-ray detectors.…”
Section: Introductionmentioning
confidence: 99%
“…Various types of perovskite structures such as three-dimensional (3D), 27,28 two-dimensional (2D), [29][30][31][32][33] one-dimensional (1D), 34,35 and zero-dimensional (0D) 36 can be realized by choosing appropriate components of the organometal halide perovskites owing to the structural tunability of these HHPs. For 0D hybrid perovskites, individual metal halide octahedra anions or metal halide clusters are completely surrounded and isolated by the organic cations.…”
Section: Introductionmentioning
confidence: 99%